Evaluating blood donor experiences and barriers/facilitators to blood donation in the United States using YouTube video content. Issue 9 (30th June 2021) - Rael, Christine Tagliaferri; Pierre, Dominique; Frye, Victoria; Kessler, Debra; Duffy, Louisa; Malos, Nick; Van Tieu, Hong
Abstract: Background: Understanding donor perception of the blood donation experience is central to maintaining an adequate blood supply. Studies that use questionnaires to assess barriers/facilitators to donation may be influenced by response bias. To address this, we conducted an innovative study integrating quantitative informatic techniques with qualitative data analysis of YouTube video content to explore donor experiences and barriers and facilitators to whole blood donation. Methods: Sampling of YouTube videos was conducted using search parameters for identifying relevant videos, based on donors' language used to describe their whole blood donation experiences (e.g., blood donation, blood donor, donated blood, gave/give blood). We eliminated duplicate videos; filtered out non‐English videos, those made outside the United States, and those with no transcripts; and restricted the time period during which videos were posted from 2015 to 2019. Search parameters were fed into a Python script, which downloaded video transcripts for all search results. The final sample was 102 noncommercial and 34 commercial transcripts. The subsequent transcriptions were uploaded into qualitative analysis software and coded two coders. A third coder randomly selected transcripts to review to ensure consistency. Results: Barriers to whole blood donation include having prior negative experiences with donation and donation‐related fear. Facilitators included altruism, having a personal connection to donation, donation center incentives, and positive experiences with blood center staff. Conclusion: Themes identified in this study were similar to those in the existing literature. This suggests that current questionnaires to address barriers/facilitators to donation are unlikely to be meaningfully impacted by response bias.